The HealthCare.gov project. Issue 2 (November 2016) - Gogan, Janis L; Davidson, Elizabeth J; Proudfoot, Jeffrey
This case describes the development of the HealthCare.gov website front-end, systems and databases supporting the implementation of the Affordable Care Act. In late October 2013, US Health and Human Services Secretary Kathleen Sebelius and US Centers for Medicare and Medicaid Services Administrator Marilyn Tavenner appear before a Congressional subcommittee to apologize about system glitches. The case gives students an opportunity to consider project risks that affected this huge systems development effort, and to consider how to ensure that millions of uninsured or underinsured Americans would be able to sign up for affordable health insurance.